(untitled) (Bioresearch Communications, 2025)
Background: The transplantation of human amniotic membrane (HAM) is a significant accomplishment in the fields of cosmetic surgery, ocular surgery, epidermis, abdominal and vaginal reconstruction, and cosmetic surgery, as it has the potential to save thousands of lives annually. Nevertheless, the risk of infectious disease transmission using amniotic membrane allografts is a significant concern, as microorganisms can be introduced into the grafts during tissue procurement. Objectives: This study aimed at the genotypic characterization of the multidrug-resistant (MDR) membrane-associated bacteria and determining the isolates’ radiation sensitivity pattern. Methods: A total of 163 bacteria retrieved from 10 amnion samples (5 from vaginal and 5 from cesarean) were subjected to biochemical and genotypic characterization. Antimicrobial and radiation sensitivity patterns of the isolates from different genotypes were determined after exposure to 60Co Gamma irradiation. Findings: Cultured bacteria were distinguished into diverse genera belonging to Enterobacter spp., Pseudomonas spp., Stenotrophomonas spp., Bacillus spp., and Staphylococcus spp. as detected by ARDRA (Amplified Ribosomal RNA Restriction Analysis) followed by 16S rRNA gene sequencing. Isolates showed highest resistance against Cefixime (100%) followed by Ampicillin (77.5%), Ceftriaxone (72.5%), Amoxicillin (70%), Cefuroxime (67.5%), Colistin (65%), Vancomycin (52.5%), Streptomycin 40%), Ciprofloxacin (32.5%), Gentamicin (27.5%), Azithromycin (25%) and Imipenem (7.5%). The D10 value for Gram-positive bacteria was higher than that of Gram-negative ones. The survival fraction indicated that the decimal reduction rate of the bacterial level decreased as the radiation dose was increased. Two strains of Gram-positive bacteria, Staphylococcus spp. (NS2 8 and NS2 21) and one strain of Bacillus spp. (CS8 2) were found to survive at 7 KGy Gamma irradiation. These findings suggested that an 8 KGy irradiation dose was enough to eradicate the bacterial load of the samples. Conclusions: This investigation reports the genotypes and radiation sensitivity pattern of AM-associated MDR bacteria, which might be necessary for determining a suitable radiation dose to eliminate the bacteria without hampering the sterility assurance level (SAL). Bioresearch Commu. 11(2): 1787-1800, 2025 (July)